2003
DOI: 10.1046/j.1365-2745.2003.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Late‐glacial and Holocene climatic effects on fire and vegetation dynamics at the prairie–forest ecotone in south‐central Minnesota

Abstract: Summary 1Treeline ecotones, such as the prairie-forest boundary, represent climatically sensitive regions where the relative abundance of vegetation types is controlled by complex interactions between climate and local factors. Responses of vegetation and fire to climate change may be tightly linked as a result of strong feedbacks among fuel production, vegetation structure and fire frequency/severity, but the importance of these feedbacks for controlling the stability of this ecotone is unclear. 2 In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 82 publications
(216 reference statements)
9
93
1
Order By: Relevance
“…In this biome, wildfires appear to have been fuel-limited throughout the period since the LGM. This was also true in Iberia during the Last Glacial period (Daniau et al, 2007) and in the North American prairie where clear links have been identified between phases of greater humidity promoting vegetation growth, increasing fuel load and fire occurrence (Brown et al, 2005;Camill et al, 2003). This relationship stands in contrast to that in better watered and more wooded environments in Mediterranean regions, such as Italy, where microcharcoal records indicate that landscape burning was most frequent during climatically arid phases of the Holocene, showing that here wildfires were not fuel-limited (Sadori and Giardini, 2007;Vannière et al, 2008).…”
Section: Resultsmentioning
confidence: 82%
“…In this biome, wildfires appear to have been fuel-limited throughout the period since the LGM. This was also true in Iberia during the Last Glacial period (Daniau et al, 2007) and in the North American prairie where clear links have been identified between phases of greater humidity promoting vegetation growth, increasing fuel load and fire occurrence (Brown et al, 2005;Camill et al, 2003). This relationship stands in contrast to that in better watered and more wooded environments in Mediterranean regions, such as Italy, where microcharcoal records indicate that landscape burning was most frequent during climatically arid phases of the Holocene, showing that here wildfires were not fuel-limited (Sadori and Giardini, 2007;Vannière et al, 2008).…”
Section: Resultsmentioning
confidence: 82%
“…In BC (i.e., at sites 5, 6, 7, 8, and 10), an inverse relationship in fire and fuels is apparent because biomass burning increased as closed mixed conifer forests were replaced by more open forests (44). Charcoal influx is often opposite to AP in the Midwest as well, where grass abundance (low woody biomass) is a good predictor of biomass burning (45). Important changes in woody fuel levels in AK are obscured in the AP trends, because AP does not show changes in the relative importance of shrubs versus trees.…”
Section: Resultsmentioning
confidence: 99%
“…Although modest shifts in the Holocene mean location of the ecotone have been inferred, studies of Holocene pollen from area lakes and bogs imply little net change in the vegetation cover of the local study region in southwestern Wisconsin and northwestern Illinois (Davis, 1977;Maher, 1982;Bartlein et al, 1984;Baker et al, 1992). Somewhat more extensive changes in local vegetation cover have been reported for lower relief, glaciated landscapes on the western margin of the ecotone in northeast Iowa and southeastern Minnesota (Baker et al, 2002;Camill et al, 2003), but hydrologic responses to Holocene environmental changes in the study area were mainly driven by direct effects of climate on precipitation and snowmelt rather than to changes in vegetation cover (Knox, 1985). Detailed descriptions of the mosaic of grassland and forest that covered the Zinc-Lead District and adjacent areas at the time of mining and agriculture settlement are presented in field maps and notes of the Federal Land Survey of the early 1830s and in other early maps and landscape sketches (Schockel, 1917;Owen, 1844Owen, , 1852Friis, 1969).…”
Section: Euro-american and Other Human Influences On The Landscapementioning
confidence: 97%